A New Decision Method of Filling Ratio Based on Energy Matching of Surrounding Rock and Backfill. (5th August 2020) - Zhou, Yanlong; Zhou, Keping; Lin, Yun
Abstract : In order to simplify the ratio decision process of cemented backfill in underground mines and achieve fine decision of filling ratio, the research on the energy matching between surrounding rock and cemented backfill in underground mines was conducted in this study. Based on the cubic function strength model of cemented backfill, the peak specific energy equation of backfill was improved by inversion analysis of the data of filling ratio experiment, and the functional relationship between the peak specific energy and the filling ratio was obtained by regression analysis. Then, based on the energy balance principle between the deformation energy released by the excavation of the underground rock mass and the peak specific energy of the cemented backfill, considering the physical and mechanical parameters of the surrounding rock of the goaf, including bulk density, elastic modulus, and burial depth, a ratio decision model of cemented backfill is established. The application results suggested that the calculation result of the model is reliable, and it can realize the rapid and accurate decision of the ratio of cement backfill in underground mines.